In vitro cancer cell-ECM interactions inform in vivo cancer treatment - Holle, Andrew W.; Young, Jennifer; Spatz, Joachim P. (Advanced drug delivery reviews, 2016)
The general progression of cancer drug development involves in vitro testing followed by safety and efficacy evaluation in clinical trials. Due to the expense of bringing candidate drugs to trials, in vitro models of cancer cells and tumor biology are required to screen drugs. There are many examples of drugs exhibiting cytotoxic behavior in cancer cells in vitro but losing efficacy in vivo, and in many cases, this is the result of poorly understood chemoresistant effects conferred by the cancer microenvironment. To address this, improved methods for culturing cancer cells in biomimetic scaffolds have been developed; along the way, a great deal about the nature of cancer cell-extracellular matrix (ECM) interactions has been discovered. These discoveries will continue to be leveraged both in the development of novel drugs targeting these interactions and in the fabrication of biomimetic substrates for efficient cancer drug screening in vitro.
Available online 17 October 2015
Gesehen am 19.05.2020